TV is the Devil, the Devil is on TV Wild Religion and Wild Media in South Africa - Scharnick-Udemans, Lee-Shae S. (2018)
In keeping with trends in the academy and the rapidly increasing presence, power, and persuasion of digital and electronic media on the African continent and in the global economy, the study of religion and the media in South Africa has become a flourishing field of intellectual inquiry. The expanse of the field in terms of approaches, both methodological and theoretical, demonstrates the multiple and complex interactions between religion and the media in a diverse range of societies and settings. In light of its recent history of apartheid and transition into democracy in the middle 1990s, when paradigmatic constitutional and political changes took place in which the relationship between religion and the media was reconstituted, the South African context, in particular, is ripe for exploring media technology and practices in relation to the political economy of the sacred. This essay pays tribute to David Chidester by testing the possibilities of his theory of 'wild religion' against two vignettes of wild media in South Africa. The first, characterized as TV is the devil explores the apartheid government's pre-emptive religiously saturated ban on television. The second example, described as the devil is on TV assesses viewers' responses to the television program, Lucifer. I argue that when read with Chidester's theorization of the 'wild ambivalence of the sacred', these examples evoke the hitherto under-explored wild character of both religion and the media.
Keywords: media politics; political economy of the sacred; Religious Diversity; wild media